Mechanism and Significance of Mirror Movements - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Neurophysiological studies, including EMG and focal magnetic brain stimulation, were used to evaluate possible mechanisms for mirror movements in 14 male patients, aged 16-60 years, with X-linked Kallmann's syndrome compared to controls at the Department of Physiology, University College London, UK.